Knowledge and Beliefs of Couples attending Marriage Counseling Centers toward correct sexual relationships - S Noohi; M Azar; AR Shafiee Kandjani; A Tajik (Tehran University of Medical Sciences, 2007)
Background & Aim: Inter-partner relationships as part of a somatic-affective interaction have important role in supporting of familial relations. In this regard, knowledge of couples about their specific role against their spouses and the ways of having correct sexual relationship is essential. This correct knowledge might help spouses to understand their husband/wife and would promote family;aposs cultural status and would be transmitted to next generations. This study carried out to determine the knowledge level and beliefs of couples attending marriage counseling centers toward correct sexual relationships. Methods & Materials: This is a cross-sectional study. A total of 300 individuals (150 couples), attending marriage counseling centers in the north and east of Tehran recruited for the study using random selection method. Data were collected using a questionnaire including knowledge and beliefs assessment questions. Results: Mean knowledge score for men and women were 12.3±2.5 and 10.1±1.8, respectively (P=0.23). Knowledge level of participants with higher education (P=0.00) and those aged 25-29 years (P=0.65) were higher than others. 11.3% of women and 13.1% of men did not have appropriate attitudes toward correct sexual relationships (P=0.35).Conclusion: Although knowledge level of respondents was just above the half of the complete score, the overall beliefs toward sexual relationships were positive.